IMPLEMENTASI KONSEP TRI HITA KARANA DALAM PRAKTEK PELAYANAN KEBIDANAN PADA PRAKTEK MANDIRI BIDAN DI WILAYAH KERJA PUSKESMAS BULELENG I: Array (LPPM STIKes Buleleng, 2020)
Midwifery services are activities providing assistance by midwives who are trained and licensed to mothers. Midwives must prioritize the delivery of midwifery services based on local wisdom or local culture so that between service providers and service recipients there is a balanced relationship. This study aims to determine the implementation or application of the concept of Tri Hita Karana in midwifery service practice in the Midwife Independent Practices in the Work Area of the Buleleng I Community Health Center. This type of research is a case study with a qualitative approach. Data is collected through observation and interviews. All participants have implemented the concept of Tri Hita Karana in Midwifery Service Practices in the Midwife Independent Practice in the Work Area of the Buleleng I Community Health Center